PREPARATION AND EVALUATION OF PARECOXIB MICROSPONGE HYDROGEL SUSTAINED RELEASED TABLET - N, Maruthi.; G, Lakshmi Radhika (Journal of Biomedical and Pharmaceutical Research, 2019)
Microsponges are the polymeric drug delivery systems composed of porous microspheres. They are tiny sponge like spherical particles that consists of myriad of inter-connecting voids within a non-collapsible structure with a large porous surface. The present work is to formulate and evaluate the Parecoxib Microsponge Hydrogel Sustained Release Tablet. The Microsponges of Parecoxib is prepared by Quasi-emulsion solvent diffusion method using Ethyl cellulose and Eudragit RS100 as polymers and Di-butyl phthalate as Plasticizer. And they are characterized for FTIR studies, production yield, particle size analysis, DSC and SEM. The production yield of formulations was from 77.77 to 82.75. FTIR and DSC studies are revealed that the drug and polymer are compatible with each other during preparation. The average diameter of Microsponge is ranged from 536.9 nm to 489.7. Parecoxib Microsponge hydrogel were prepared as sustained release tablets by using sustained release polymers like MCC, Magnesium stearate, Lactose and talc. Preformulation of Microsponge granules were carried out by various parameters and post formulation were carried out by In-vitro dissolution studies, hardness, friability and weight variation tests. Formulation F3 shows good results for the drug release kinetics as controlled release and F6 formulation shows good results for the in-vitro dissolution studies for sustained release. Key words: Microsponge hydrogel drug delivery, Parecoxib, Sustained drug release tablets, quasi emulsion solvent diffusion method.